Test of Designing and Manufacturing a Polyether Ether Ketone Endoprosthesis for Canine Extremities by 3D Printing - Mendaza-DeCal, Rosa; Peso-Fernandez, Salvador; Rodriguez-Quiros, Jesus (Frontiers in Mechanical Engineering, 2021)
Total limb amputation is quite common in small animals, although most of the indicated pathologies do not need such a restrictive procedure. Exo-endoprosthesis is a suggested alternative for enhancement of the biomechanical situation of these patients. 3D printing the internal part of exo-endoprostheses in polyether ether ketone (PEEK) is evaluated. Two different shapes of this internal part – one for radius’ and the other for cylindrical medullary cavities – were assessed. Proper PEEK temperature settings for 3D printing the internal part of exo-endoprostheses by fused filament fabrication (FFF) were obtained. Printing trials were carried out for different dimensions and printing orientation of these parts to achieve the best bone anchorage and thread strength outcomes. Pull-out strength tests for different surfaces of the internal part were performed with a best outcome for positive surfaces. All printed internal parts were inserted in canine tibiae and radii for an ex vivo assessment of bone anchorage and thread strength parameters. The best printing results were obtained at 410 ºC and 130 ºC of the nozzle and bed temperatures, respectively. Also, a positive correlation was observed between printing code, quality, and take-off time, while inverse correlation was shown between the take-off and printing code or quality, just like the print-bed temperature and printing code. The positive surfaces had the best pull-out strength outcomes. Excellent bone anchorage and thread strength outcomes were obtained for one variant of each internal part shape. Designed devices had shown good threaded rod’s fitting inside the PEEK plug and perfect bone anchorage of the PEEK plug for tibiae and radii. In addition, iteration of manufacturing PEEK small devices by FFF technology has been shown due to small standard deviation of most variants.